Regularities of the Occurrence of Geoecological Threats and Geographic Mechanisms of Their Implementation - SHCHERBATYUK, Andrey P. (Journal of Environmental Management and Tourism, 2020)
Chitino-Ingodinskaya basin of the Zabaykal type is a typical representative part of the intercontinental intermountain basins. An excess of the maximum permissible concentrations of pollutants in the atmospheric air is recorded in the cities, which are located here. One of the main areas of research within the framework of the subject under consideration is the assessment of the impact of the terrain on the benz (a) pyrene atmosphere pollution index and related indicators of demographic losses (due to respiratory disease) of the population of cities in the Zabaikalsky Krai which is located in the stagnant atmospheric circulation of valleys and intermountain basins. The evaluation of the geo-environmental threats and the geographical mechanisms of its realization are accomplished. The regularities of the manifestation of extremely dangerous concentrations of pollutants in the atmospheric air, allowing to predict the indicators of living conditions for the population, are revealed. The cause-and-effect relationships between the level of transformation of urbanized territories and the degree of discomfort of the conditions for the life of the population of cities located in hollows are studied, taking into account natural and man-made factors.